1991
DOI: 10.1007/bf02633537
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of mammographic parenchymal patterns in premenopausal Japanese and British women

Abstract: Normal premenopausal Japanese women have significantly more favourable mammographic parenchymal patterns (Wolfe Grades) than comparable British women. This finding is unaffected when the women are stratified by age, Quetelet's Index, age at menarche, age at first birth, and parity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In our study, the mean percent density was comparable in all age groups between the Caucasian and the Hispanic women. Conflicting results have been reported between the Asian women and the Caucasian women, 21,[23][24][25][26] some showing significant differences while others not. A large study using BI-RADS score to classify the subjects into fatty ͑BI-RADS 1-2͒ and dense ͑BI-RADS 3-4͒ breasts found that the Asian women had significantly denser breasts than the Caucasian women, and that the differences were greatest in the older age groups.…”
Section: Discussionmentioning
confidence: 93%
“…In our study, the mean percent density was comparable in all age groups between the Caucasian and the Hispanic women. Conflicting results have been reported between the Asian women and the Caucasian women, 21,[23][24][25][26] some showing significant differences while others not. A large study using BI-RADS score to classify the subjects into fatty ͑BI-RADS 1-2͒ and dense ͑BI-RADS 3-4͒ breasts found that the Asian women had significantly denser breasts than the Caucasian women, and that the differences were greatest in the older age groups.…”
Section: Discussionmentioning
confidence: 93%
“…A case‐control study showed that women with breast cancer were nearly 7 times as likely to be classified as one of the high‐risk Wolfe categories than controls 19. Normal premenopausal Japanese women were found to have significantly more favorable mammographic patterns (Wolfe grades20) than British women 21. Results from a mammography screening study using Wolfe's classification scheme suggest a very low prevalence of the DY (mammary dysplasia) patterns 22.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of breast cancer among nonwhite women is consistently lower than that of white women and, overall, ethnic differences in mammographic density have been found to be consistent with those for breast cancer risk [7][8][9] with the exception of one study that reported mammographic density was higher in less acculturated Asian women [10].…”
Section: Introductionmentioning
confidence: 79%